Digitalizing Arabic Teaching for Non-Native Speakers in Sri Lanka: Challenges and Opportunities - H.L.M. Mohideen; A. Abdul Rasheed (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Arabic is an important language for Muslims, as it is the language of the Quran and essential religious texts. In Sri Lanka, the Muslim community prioritizes teaching and learning Arabic to ensure a deep connection with their faith. Arabic teaching is integrated across various sectors, including Madrasas, schools, universities, and community programs. However, in Sri Lanka, Arabic teaching traditionally depends on conventional methods, but there's a pressing need for digitalization. This study aims to find the challenges associated with integrating digital technologies in Arabic language teaching for non-native speakers in Sri Lanka, to confirm the effectiveness of existing digital tools and resources in facilitating Arabic language learning in Sri Lanka, and to explore opportunities for enhancing Arabic language teaching through digital platforms in the Sri Lankan context. The researcher used descriptive and analytical methods to complete this study. To meet the objectives of the study, primary and secondary data were used with qualitative and quantitative approaches. This study addresses the challenges and opportunities in digitalizing Arabic teaching for non-native speakers in Sri Lanka. This study concluded that, by developing vast online resources and interactive platforms, suitable materials for local needs, and integrating digital assessment tools, the research highlights how digital transformation can enhance the effectiveness and accessibility of Arabic language teaching in Sri Lanka. The findings aim to provide actionable insights for policymakers, teachers, and technology developers to overcome barriers and maximize the benefits of digital learning in this context.